Hubungan Perubahan Sosial dan Perubahan Hukum Dalam Sistem Hukum Terbuka - Sainul; Oktavia, Ayu; Angkasa, Nitaria (IAIN Metro, 2024)
In social dynamics, societal heterogeneity is evident in various dimensions, including culture, ethnicity, religion, and race. This diversity affects behaviors, thinking patterns, and knowledge. Addressing these differences is crucial to fostering a shared understanding of common needs, as it prevents potential conflicts and ensures social cohesion. This study focuses on how social changes impact legal reforms within an open legal system framework. The research employs a qualitative, normative juridical method, emphasizing doctrinal research and library research to analyze how legal systems adapt to social changes. Results indicate that for legal changes to be effective, they must align with local wisdom and accommodate modernization, ensuring the legal system remains dynamic and responsive. The study concludes that an open legal system is essential for aligning legal reforms with Indonesian values and societal needs.